Dasatinib-induced pulmonary hypertension in acute lymphoblastic leukemia: case report - Gülten Taçoy; Atiye Çengel; Zübeyde Nur Özkurt; Sedat Türkoğlu (KARE Publishing, 2015)
Pulmonary hypertension (PHT) is a pathological condition determined as an increase in mean pulmonary arterial pressure ≥25 mmHg. Pulmonary arterial hypertension (PAH) is precapillary PHT and a life-threatening disease group which consists of different etiologies with the same pathological and clinical findings, and which is characterized by elevated pulmonary vascular resistance. Dasatinib is a dual Src/Abl kinase inhibitor associated with higher affinity for BCR/ABL kinase than imatinib, and is used in the treatment of chronic myelocytic leukemia and Philadelphia chromosome positive acute lymphoblastic leukemia (ALL). We describe a case with ALL, in whom dasatinib treatment induced PAH, and who recovered with bosentan treatment.